2019
DOI: 10.1177/0956797619838763
|View full text |Cite
|
Sign up to set email alerts
|

Differentiate to Regulate: Low Negative Emotion Differentiation Is Associated With Ineffective Use but Not Selection of Emotion-Regulation Strategies

Abstract: Emotion differentiation, which involves experiencing and labeling emotions in a granular way, has been linked with well-being. It has been theorized that differentiating between emotions facilitates effective emotion regulation, but this link has yet to be comprehensively tested. In two experience-sampling studies, we examined how negative emotion differentiation was related to (a) the selection of emotion-regulation strategies and (b) the effectiveness of these strategies in downregulating negative emotion ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
169
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(189 citation statements)
references
References 37 publications
11
169
2
Order By: Relevance
“…Emotional awareness reflects one's subjective understanding of their emotional state (Lane & Schwartz, 1987;Lumley, Neely, & Burger, 2007). Emotional awareness is central to the experience of discrete emotions (Barrett, 2006) and is thought to be a prerequisite to many forms of effective emotion regulation (Barrett, Gross, Christensen, & Benvenuto, 2001;Kalokerinos, Erbas, Ceulemans, & Kuppens, 2019). Low emotional awareness is associated with many forms of psychopathology (Deborde, Vanwalleghem Maury, & Aitel, 2015;Frewen, Dozois, Neufeld, & Lanius, 2008;Hendryx, Haviland, & Shaw, 1991), suggesting that it may represent a transdiagnostic factor associated with increased vulnerability for psychopathology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional awareness reflects one's subjective understanding of their emotional state (Lane & Schwartz, 1987;Lumley, Neely, & Burger, 2007). Emotional awareness is central to the experience of discrete emotions (Barrett, 2006) and is thought to be a prerequisite to many forms of effective emotion regulation (Barrett, Gross, Christensen, & Benvenuto, 2001;Kalokerinos, Erbas, Ceulemans, & Kuppens, 2019). Low emotional awareness is associated with many forms of psychopathology (Deborde, Vanwalleghem Maury, & Aitel, 2015;Frewen, Dozois, Neufeld, & Lanius, 2008;Hendryx, Haviland, & Shaw, 1991), suggesting that it may represent a transdiagnostic factor associated with increased vulnerability for psychopathology.…”
mentioning
confidence: 99%
“…Two potential pathways could explain these associations. First, low emotional awareness may disrupt the ability to regulate emotions (Barrett et al, 2001;Kalokerinos et al, 2019). Second, because low emotional awareness is associated with more difficulty recognizing emotions in others (Grynberg et al, 2012), low emotional awareness could impair social functioning and in turn contribute to multiple forms of psychopathology (Collin, Bindra, Raju, Gillberg, & Minnis, 2013).…”
mentioning
confidence: 99%
“…Finally, the current study examined how emotion differentiation related to broader internalizing problems, as opposed to focusing on symptoms of depression alone. Whereas many studies have examined emotion differentiation specifically in relation to depression (Demiralp et al, 2012;Erbas et al, 2019Erbas et al, , 2014Kalokerinos et al, 2019;Liu, Gilbert, & Thompson, 2020;Mankus, Boden, & Thompson, 2016;Starr, Hershenberg, Li, & Shaw, 2017;Starr et al, 2019;Willroth, Flett, & Mauss, 2019), only a single study has examined emotion differentiation in generalized anxiety disorder (Decker, Turk, Hess, & Murray, 2008). Interestingly, that study found that mean levels of emotion differentiation do not differ between individuals who do or do not have generalized anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…From this view, high emotion differentiation emerges when individuals have highly granular emotion concepts, allowing people to construct a specific understanding of what they're feeling in terms of: (i) the underlying causes and characteristics that give rise to each emotional experience and (ii) how to implement regulatory strategies that will best ameliorate a given emotional experience in any specific situation (Barrett et al, 2001;Kashdan et al, 2015;Nook et al, 2020). Consequently, analyzing and responding to one's emotional experiences using such "granular" emotion concepts and words is thought to boost adaptive responding to negative emotions (Kalokerinos et al, 2019;Kashdan et al, 2015), which are commonly induced by stressful experiences (Bolger et al, 1989;Mroczek & Almeida, 2004). This, in turn protects individuals from developing maladaptive regulatory habits (e.g., worrying, avoidance, and rumination) that can contribute to internalizing problems (Aldao et al, 2010;Kircanski, Thompson, Sorenson, Sherdell, & Gotlib, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation